Work patterns and a tendency among Polish nurses to leave their job - Dorota Kilańska; Aleksandra Gaworska-Krzemińska; Agnieszka Karolczak; Piotr Szynkiewicz; Małgorzata Greber (Nofer Institute of Occupational Medicine, 2019)
Background Work patterns are important factors in employees' decisions to change their job or leave their profession. The majority of nurses in Poland are women who play other social roles besides work. For this reason, satisfaction with their work patterns including input into work schedules, has a particularly significant impact on considering the idea of quitting their job. Material and Methods The study was conducted in 2008-2011 in 8 out of 10 higher education institutions which train nurses. Data obtained from 1045 questionnaires collected from a total of 1049 respondents from 3 randomly selected higher education institutions was used in this research paper. The relationship between the qualitative features and dichotomus quality features under examination was assessed using univariate and multivariate logistic regression models. Results The results of the univariate logistic regression indicate that the risk of quitting increases to the highest extent with a mixed work pattern; it is lower for 12/24 h, and slightly lower for 2 day/night shifts. Conclusions A pattern with a single day shift was adopted as the reference level to reduce the risk of Polish nurses' quitting their job. Med Pr. 2018;70(2):145-53